IMPLEMENTATION OF POLICIES CONCERNING MANAGEMENT AND ENGINEERING OF TRAFFIC AND ROAD TRANSPORTATION AND PARKING IN UBUD SUB-DISTRICT - Artayasa, I Made (E-Journal of Cultural Studies; Vol 16 No 4 (2023): Volume 16 Number 4 November 2023DO - 10.24843/cs.2023.v16.i04.p05, 2023)
Management and engineering of traffic and road transportation are programs initiated by the Gianyar Regency government with the aim of achieving an integrated transportation system that ensures safety, security, order, smoothness, regularity, success, utility, comfort, and efficiency throughout the Ubud sub-district and its surrounding areas. This policy aligns with the community’s purchasing power, public interest aspects (road users), environmental sustainability, spatial planning, and advancements in knowledge and technology. The research addresses the following issues: 1) how is the implementation of policies on traffic management, road transportation engineering, and parking in Ubud sub-district, 2) what factors hinder the implementation of traffic management, road transportation engineering policies, and parking in Ubud sub-district? The research employs a descriptive qualitative approach, using the theory proposed by Merilee S. Grindle. The findings indicate that the management and engineering of traffic and road transportation, as well as parking, are not yet one hundred percent effective due to inadequate infrastructure, such as parking spaces for residents, workers, and tourists, and a lack of personnel both from the police and the Gianyar Regency Transportation Agency. Keywords : Policy, Implementation, Management